Zirconium-catalyzed direct amide bond formation between carboxylic esters and amines. Issue 34 (26th August 2015) - Lenstra, Danny C.; Nguyen, D. Thao; Mecinović, Jasmin
Abstract: Development of catalytic amide bond formation reactions from readily available starting materials remains a challenging task for modern organic chemistry. Herein, we report that unactivated carboxylic esters and amines react in the presence of 10 mol % of zirconocene dichloride (Cp2 ZrCl2 ) in toluene at 110 °C to afford amides in very good to excellent conversions. The Zr-catalyzed reaction is amenable for the amidation of aliphatic and aromatic carboxylic esters with primary and secondary amines. The reaction proceeds with almost complete retention of configuration for chiral esters and chiral amines. Graphical abstract: